2004
DOI: 10.1158/1078-0432.ccr-04-0005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Radiation and Ibuprofen on Normoxic Renal Carcinoma Cells Overexpressing Hypoxia-Inducible Factors by Loss of von Hippel–Lindau Tumor Suppressor Gene Function

Abstract: Purpose: Tumor hypoxia is a major limiting factor for radiation therapy. Hypoxia-inducible factors (HIFs) are overexpressed in several human cancers and are considered prognostic markers and potential targets for cancer therapy. The purpose of the present study was to investigate the impact of HIFs on radiosensitivity.Experimental Results: The data showed only small differences in the radiosensitivity between the cells overexpressing HIFs and cells with basal HIF levels. The dose-modifying factors for C2, 786-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 42 publications
0
24
0
1
Order By: Relevance
“…[1][2][3][4] Although HIF-1a level is good indicator of poor outcome in clinical data, evidence of the role of HIF-1a in hypoxia-related radiation and drug resistance is inconsistent because of different oxygen concentration and cell lines used in experiments. [5][6][7][8][9][10] HIF-1 knockdownmediated radiation or drug sensitization under normoxia produced negative results in some studies since HIF-1 was expected to play minor roles in the presence of O 2 . Cells with normal or suppressed HIF-1 status were not indicated as the major part of therapy barrier under normoxia.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Although HIF-1a level is good indicator of poor outcome in clinical data, evidence of the role of HIF-1a in hypoxia-related radiation and drug resistance is inconsistent because of different oxygen concentration and cell lines used in experiments. [5][6][7][8][9][10] HIF-1 knockdownmediated radiation or drug sensitization under normoxia produced negative results in some studies since HIF-1 was expected to play minor roles in the presence of O 2 . Cells with normal or suppressed HIF-1 status were not indicated as the major part of therapy barrier under normoxia.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Ugurel and coworkers suggests that angiogenic factors like VEGF are useful predictive serum markers for survival (22). On the other hand, the measurement of angiogenic factors in serum can be of interest for the evaluation of the effects of antiangiogenic treatments (13) and particularly those targeting HIF-1␣ (24). It is known that the cellular half-life of HIF-1␣ is very short (17).…”
Section: Resultsmentioning
confidence: 99%
“…Nonquantitative Western blotting analysis is the sole technique which can be used in such conditions. Experimental studies into HIF-1␣ are currently expanding (13), and targeted therapies directed specifically to HIF-1␣ are being developed (19,25). There is thus a need, in preclinical pharmacological studies, to measure more precisely the level of HIF-1␣ expression as a function of the dose and/or time of antiangiogenic treatments in tumor cells.…”
mentioning
confidence: 99%
“…A clinical study of radiation treatment for head and neck cancer reported that levels of both HIF1α and HIF2α correlated with radiation resistance [9]. However, in experiments by Palayoor et al [16], transfection of VHL into RCC cells lacking this gene did not alter radiation sensitivity, despite leading to an increase in protein levels for both HIF1α and HIF2α. One possible reason for the difference in the present results and that obtained by Palayoor et al may be due to the pleiomorphic effects of VHL on gene expression.…”
Section: Discussionmentioning
confidence: 98%